2022
DOI: 10.3389/fimmu.2022.792684
|View full text |Cite
|
Sign up to set email alerts
|

The CCR5 Gene Edited CD34+CD90+ Hematopoietic Stem Cell Population Serves as an Optimal Graft Source for HIV Gene Therapy

Abstract: Transplantation of allogenic hematopoietic stem and progenitor cells (HSPCs) with C-C chemokine receptor type 5 (CCR5) Δ32 genotype generates HIV-1 resistant immune cells. CCR5 gene edited autologous HSPCs can be a potential alternative to hematopoietic stem cell transplantation (HSCT) from HLA-matched CCR5 null donor. However, the clinical application of gene edited autologous HSPCs is critically limited by the quality of the graft, as HIV also infects the HSPCs. In this study, by using mobilized HSPCs from h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 62 publications
0
5
0
1
Order By: Relevance
“…Следует отметить, что на степень приживления ГСК человека у мышей NBSGW оказывают влияние многие факторы. Среди них можно указать пол животных-реципиентов, источник и дозу ГСК, способ мобилизации ГСК для выделения из периферической крови, индивидуальные особенности донора (возраст), присутствие в трансплантате примеси иммунных клеток донора и даже степень его обогащенности длительно репопулирующими ГСК [15][16][17][18][19][20][21][22]. Помимо учета перечисленных выше факторов разработка протоколов доклинической оценки безопасности продуктов генной и клеточной терапии на основе ГСК включает в себя оценку необходимого количества животных для исследования, распределение животных в группах по возрасту и полу.…”
Section: Discussionunclassified
“…Следует отметить, что на степень приживления ГСК человека у мышей NBSGW оказывают влияние многие факторы. Среди них можно указать пол животных-реципиентов, источник и дозу ГСК, способ мобилизации ГСК для выделения из периферической крови, индивидуальные особенности донора (возраст), присутствие в трансплантате примеси иммунных клеток донора и даже степень его обогащенности длительно репопулирующими ГСК [15][16][17][18][19][20][21][22]. Помимо учета перечисленных выше факторов разработка протоколов доклинической оценки безопасности продуктов генной и клеточной терапии на основе ГСК включает в себя оценку необходимого количества животных для исследования, распределение животных в группах по возрасту и полу.…”
Section: Discussionunclassified
“…The development of mobilization-based chemotherapy-free HSPC transplantation and concomitant overexpression of homing/engraftment enhancers for early engraftment is expected to improve the success rates of HSPC gene editing ( Felker et al, 2022 ; Omer-Javed et al, 2022 ). The ex vivo culture-free HSPC gene editing and gene editing of a sub-population of HSPCs can potentially simplify the gene therapy approach ( Radtke et al, 2020 ; Karuppusamy et al, 2022 ; Venkatesan et al, 2023 ). Gene editing delivery tools have played a substantial role in the success of HSPC gene editing; however, they are also a cause of the high cost of HSPC gene therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclosporin A (CsA) and rapamycin cause a delay in proliferation, while PGE2 reduces the CD34 + CD90 + primitive cell population ( Wang et al, 2014 ; Petrillo et al, 2018 ; Schott et al, 2019 ). We have shown that culturing HSPCs with a cocktail of small molecules, resveratrol, UM171, and SR1 increases the frequency of gene-modified stem cells ( Christopher et al, 2022 ; Karuppusamy et al, 2022 ). Vesicular stomatitis virus envelope glycoprotein (VSV-G) pseudotypes from wild-type HIV provide a powerful tool for cargo delivery ( Duvergé and Negroni, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…HIV-1 infection can lead to impaired hematopoietic function of HSPCs in several ways. First, a large body of evidence indicates that low levels of CD4 receptors expressed by HSPCs can be targeted by HIV thereby leading to impaired function ( Sebastian et al, 2017 ; Chen, 2019 ; Karuppusamy et al, 2022 ). Second, HIV-1-produced Nef proteins expressed in HSPCs impeding the development and production of myeloid–erythroid cells and inducing apoptosis ( Zou et al, 2021 ).…”
Section: Potential Mechanisms Of Incomplete Immune Reconstitutionmentioning
confidence: 99%